Discrete event simulation–based energy efficient path determination scheme for probabilistic voting–based filtering scheme in sensor networks - Su Man Nam; Tae Ho Cho (International Journal of Distributed Sensor Networks)
In wireless sensor networks, sensors are extremely vulnerable to false positive and false negative attacks due to their stringent energy and computational constraints. Several en-route filtering schemes mainly focus on saving energy through early detection of false data within a short distance against these attacks; however, they cannot immediately block the false data injected by compromised nodes. A security scheme uses context-aware architecture for a probabilistic voting–based filtering scheme to detect the compromised nodes and block the injection of false data, unlike security protocols. Although these schemes effectively obstruct the false data forwarding, they cannot make any detour around the compromised node to avoid it during data forwarding. In this article, we propose a discrete event simulation–based energy efficient path determination scheme that takes a detour around the compromised node against the attacks. Our proposed scheme extracts candidate paths considering the network status and selects a path with the highest energy efficiency from among the candidates using discrete event simulation. Simulation results indicate that the proposed scheme provides energy savings of up to 12% while maintaining the security strength against the two attacks compared to the existing schemes.